An empirical review: Characteristics of plant microsatellite markers that confer higher levels of genetic variation1. (17th August 2015) - Merritt, Benjamin J.; Culley, Theresa M.; Avanesyan, Alina; Stokes, Richard; Brzyski, Jessica
Abstract : During microsatellite marker development, researchers must choose from a pool of possible primer pairs to further test in their species of interest. In many cases, the goal is maximizing detectable levels of genetic variation. To guide researchers and determine which markers are associated with higher levels of genetic variation, we conducted a literature review based on 6782 genomic microsatellite markers published from 1997–2012. We examined relationships between heterozygosity ( H e or H o ) or allele number ( A ) with the following marker characteristics: repeat type, motif length, motif region, repeat frequency, and microsatellite size. Variation across taxonomic groups was also analyzed. There were significant differences between imperfect and perfect repeat types in A and H e . Dinucleotide motifs exhibited significantly higher A, H e, and H o than most other motifs. Repeat frequency and motif region were positively correlated with A, H e, and H o, but correlations with microsatellite size were minimal. Higher taxonomic groups were disproportionately represented in the literature and showed little consistency. In conclusion, researchers should carefully consider marker characteristics so they can be tailored to the desired application. If researchers aim to target high genetic variation, dinucleotide motif lengths with large repeat frequencies may be best.